(untitled) (Ustozlar uchun, 2025)
Actually, relative clauses are important components of complex sentences They add depth and nuance to English communication. Some students get confused with differentiating these two. Generally, the differences between defining (restrictive) and non-defining (non-restrictive) relative clauses frequently challenges learners. This article will provide and explain for educators with a practical and effective guide to teaching these clauses effectively by focusing on their function, structure, and punctuation.